Sobre a estabilidade de catalisadores de cobalto suportados durante a reforma do etanol - Ávila Neto, Cícero Naves de (2012)
Cobalt-based catalysts supported on γ-alumina and magnesium aluminate modified with lanthanum and cerium have been applied to various conditions of reforming of ethanol. The initial challenge was to control the rate of carbon accumulation, a major cause of deactivation of catalysts under steam reforming of ethanol. In situ X-ray absorption spectroscopy analyses showed that the rate of carbon accumulation is inversely proportional to the amount of Co2+ species and directly proportional to the amount of Co0 species. X-ray photoelectron spectroscopy analyses showed that, after reducing the catalysts in hydrogen, the oxidized fraction of the particles is mainly on their surface. Both the oxidized and reduced fractions of cobalt crystallites have face-centered cubic structure. The concentration of superficial oxygen under reforming conditions is determined by the curvature of the surface of the particles, the nature of the supports and the presence of promoters such as platinum and copper. The concentration of superficial oxygen is also highly sensitive to reaction conditions such as the composition and amount of oxidizing agents, such as oxygen and water, and reaction temperature. The rate of accumulation of carbon could be controlled with co-feeding oxygen to the reactor, process called oxy-reforming of ethanol, and using ceria as support. However, stability tests showed that catalyst deactivation may also occur by oxidation of metal sites. The ignition of the reforming process takes place in a microregion at the entrance of the catalyst bed where ethanol is fully oxidized, releasing energy and increasing the local temperature. Spatial-resolved X-ray absorption spectroscopy analyses showed that the ratio Co2+/Co0 is much greater than one inside this microregion. The high local temperature and the presence of oxidized species in the entrance of the bed produce the appropriate conditions which lead the Co2+ ions to diffuse into the defect spinel structure of γ-alumina, leading to loss of potentially active sites for reforming of ethanol. This phenomenon is unleashed as a wave that propagates from the entrance of the bed downstream to the regions where Co2+ species exist. However, one can prevent the diffusion of Co2+ species to the structure of γ- alumina using aluminates as supports.